2008
DOI: 10.1002/ejic.200800243
|View full text |Cite
|
Sign up to set email alerts
|

β‐Diketonate, β‐Ketoiminate, and β‐Diiminate Complexes of Difluoroboron

Abstract: A series of β‐diketonate, keto(aryl)iminato, and β‐bis(aryl)iminato complexes of difluoroboron, twenty in total, have been prepared to assess the impact of chelate ring and aniline substitution on the structural, electrochemical, and photophysical properties of these ubiquitous chelates. DFT (B3LYP/6‐31G*) calculations supplemented the experimental results and both demonstrated that replacing oxygen with the more electron‐donating aniline groups serves to only fine‐tune the electronic properties because both t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
2
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(71 citation statements)
references
References 45 publications
4
63
2
2
Order By: Relevance
“…Gardinier et al have reported the synthesis of boron keto(aryl)iminates and their optical behaviors. 121 The emissions of these boron compounds were strong in the solid states, and they became weaker in the solution states. This phenomenon inspired us to explore the potential of new AIEactive materials.…”
Section: ¹1mentioning
confidence: 99%
“…Gardinier et al have reported the synthesis of boron keto(aryl)iminates and their optical behaviors. 121 The emissions of these boron compounds were strong in the solid states, and they became weaker in the solution states. This phenomenon inspired us to explore the potential of new AIEactive materials.…”
Section: ¹1mentioning
confidence: 99%
“…A comparison study between boron diketonate and related chelate complexes with regard to their electronic structures was systematically performed by Gardinier and her co-workers. 48 By replacing one of the oxygen atoms with a nitrogen atom, the functional group could be incorporated. In addition, a distortion was introduced into the molecules using the relatively weaker B-N bond compared with the B-O bond.…”
Section: Emissive Solid Materials Based On the Aie Propertymentioning
confidence: 99%
“…Boron diketonate exhibited a strong blue emission in tetrahy- The AIE behaviors of boron ketoiminates can be significantly increased by the crystal packing structures present. Based on X-ray single-crystal analyses, it was shown that the molecular structure of diketonate was highly planar, while ketoiminates included asymmetric structures and particularly distortion in the complex that originated from relatively longer bond lengths of B-N. 48 These data indicate that the boron-chelating rings on ketoiminates should be more flexible than those on diketonates; therefore, consumption of excitation energy by molecular tumblings should occur in the solution state. As a result, a small emission was observed from the solutions containing ketoiminates.…”
Section: Emissive Solid Materials Based On the Aie Propertymentioning
confidence: 99%
“…Their optical [1][2][3][4][5][6][7][8][9][10][11] and electrochemical [11][12][13][14][15][16] properties have been described in previous studies and it has been shown that they can be used as versatile uorophores, 1-5 electron acceptors 17,18 in one-electron transfer processes 19 or in chargetransport materials in both organic eld effect transistors and organic light emitting diodes. [20][21][22][23][24][25] One-electron reduction proceeds via the formation of a radical anion where the unpaired electron is delocalized on the p-system of the boroncontaining six-membered chelate ring, as demonstrated by electron paramagnetic resonance studies.…”
Section: Introductionmentioning
confidence: 99%